Educational Service Strategies for the Communication Methods of Children with Autism - Ananda Kharomatul Auliyah; Regina Maharani; Ainur Rizqi (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2025)
This study is grounded in the importance of communication as a fundamental aspect of learning and social interaction, particularly for children with autism who often face significant communication challenges. The purpose of this research is to identify and analyze the effectiveness of educational service strategies in supporting the communication development of children with autism at Yayasan Cinta Ananda. This study employs a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving teachers who directly engage with children on the autism spectrum. The analysis was conducted by organizing, reducing, and interpreting data to identify patterns and key themes related to communication strategies and their implementation in the learning process. The findings reveal that adaptive and individualized strategies are effectively applied, supported by the use of visual aids and the active role of teachers as facilitators. These strategies contribute to improved communication skills, increased interaction, and greater confidence among students. However, limitations such as varying student abilities, limited resources, and the need for continuous teacher development were also identified. In conclusion, educational service strategies at Yayasan Cinta Ananda are effective in enhancing communication skills among children with autism, although continuous improvement is required to address existing challenges.